2002
DOI: 10.1007/s00259-002-0798-1
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrine transporter density as a causative factor in alterations in MIBG myocardial uptake in NIDDM model rats

Abstract: Cardiac scintigraphic studies with iodine-123 labeled metaiodobenzylguanidine ([(123)I]MIBG) have demonstrated global and regionally pronounced decreases in myocardial accumulation of radioactivity in diabetes. The aim of this study was to investigate the cause of the regional differential decrease in accumulation. To this end, we investigated the global and regional myocardial distribution of [(125)I]MIBG in GK/Crj (GK) rats [a model of non-insulin-dependent diabetes mellitus (NIDDM)] and assessed the respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 37 publications
0
18
1
Order By: Relevance
“…One study, however, found similar cardiac MIBG uptake between the anterior and inferior regions of the rat heart in a model of non-insulin dependent DM. 42 We cannot plausibly explain these disparate results, including those of the present study. However, differences in the MATSUKI A et al…”
Section: Cardiac Mibg Accumulationcontrasting
confidence: 67%
See 1 more Smart Citation
“…One study, however, found similar cardiac MIBG uptake between the anterior and inferior regions of the rat heart in a model of non-insulin dependent DM. 42 We cannot plausibly explain these disparate results, including those of the present study. However, differences in the MATSUKI A et al…”
Section: Cardiac Mibg Accumulationcontrasting
confidence: 67%
“…Impaired cardiac norepinephrine uptake in diabetic hearts determined using MIBG or 11 C-hydroxyephedrine is accompanied by decreases in cardiac norepinephrine transporter density 42 and nerve growth factor protein. 43 The etiology of cardiac sympathetic nerve dysfunction in DM remains unclear, but the following mechanisms have been proposed: (1) degeneration of proteins critical to neural function by non-enzymatic glycosylation; 44 (2) reduction of neurotrophic factors; 45 (3) altered neural polyol metabolism; 10 and (4) microvascular disease with impaired blood flow.…”
Section: Cardiac Mibg Accumulationmentioning
confidence: 99%
“…A report noted that in a diabetic rat model, both cardiac and plasma norepinephrine levels were unchanged between diabetic and control rats, but decreased 123 I-MIBG-derived myocardial radioactivity was related to diminished transporter density. 17 Other animal studies have reported increased cardiac uptake-1 expression in the setting of high norepinephrine concentrations. 18,19 Moreover, downregulation of the transporter by pheochromocytoma would not explain normal 6-[…”
Section: Discussionmentioning
confidence: 97%
“…Once carried to the nervous terminals, the tracer is taken up by cardiac sympathetic neurons and stored in adrenergic vesicles via a specific norepinephrine transporter (NET) (9)(10)(11)(12)(13)(14)(15). Using this tool, several clinical studies (4,5,16,17) documented an accelerated tracer washout from the heart that was experimentally found to be an index of impaired norepinephrine reuptake due to reduced NET expression in the diabetic myocardium (18)(19)(20). Most of these studies, however, also reported that such an accelerated cardiac loss of MIBG was associated with a relatively preserved initial uptake in most diabetic patients (4,5,16,17), especially when tracers with high specific activity were used (21).…”
mentioning
confidence: 99%